Perovskite solar cell internal packaging method based on in-situ polymerization

By introducing acrylates and thermal initiators into the perovskite layer for in-situ polymerization, the sensitivity of perovskite solar cells to humidity and mechanical external stress is solved, the stability is significantly improved and lead leakage is suppressed, and calcium is achieved Efficient application of titanium-based solar cells.

CN119277937APending Publication Date: 2025-01-07NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411388279.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Perovskite solar cells are sensitive to humidity and mechanical external stress, resulting in insufficient stability, and lead-based perovskites have a risk of lead leakage, limiting their commercial applications and the use of flexible devices.

Method used

Acrylates and micro-caloric initiators are introduced into the perovskite layer, and in situ polymerization is carried out through the annealing process to form a hydrophobic polymer structure, improve water vapor resistance and mechanical properties, and inhibit lead leakage.

Benefits of technology

It significantly improves the humidity stability and mechanical stability of perovskite solar cells, effectively inhibits lead leakage, improves biosafety, and maintains more than 90% of the battery efficiency under the relative humidity conditions of 75%±5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119277937A_ABST
    Figure CN119277937A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of perovskite solar cells, in particular to a perovskite solar cell internal packaging method based on in-situ polymerization, and the method comprises the following steps: S1, preparing a first charge transmission layer on a conductive substrate; s2, a perovskite layer is prepared on the first charge transport layer in the S1, a polymer inner packaging layer is introduced into the perovskite layer, and the polymer inner packaging layer is formed by polymerization reaction of acrylic ester and a thermal initiator; s3, preparing a charge transport layer II on the perovskite layer in the S2; and S4, preparing a back electrode on the charge transport layer 2 in the S3. Acrylate and a thermal initiator are introduced into a perovskite precursor, polymerization can be rapidly completed in the perovskite annealing process, and a formed polymer structure can improve the water vapor resistance of a perovskite layer and can counteract part of external stress, so that the humidity stability and mechanical stability of the perovskite solar cell are improved; the lead leakage of the lead-based perovskite solar cell can be effectively inhibited, and the biological safety is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to an internal packaging method of a perovskite solar cell based on in-situ polymerization. Background Art

[0002] As the third generation of solar cells, perovskite solar cells have the advantages of relatively excellent photoelectric properties (such as high light absorption coefficient, adjustable band gap, etc.), low preparation cost, and relatively simple preparation process. They are expected to replace traditional silicon solar cells or be made into stacked cells with silicon cells. Therefore, they have attracted widespread attention and have developed rapidly in the past decade. However, the perovskite material itself is very sensitive to the external environment (such as oxygen, humidity, heat, etc.). Especially in the face of humidity, the perovskite material will react with water vapor to produce some easily dissipated products, which will lead to irreversible decomposition and eventually cause the failure of the perovskite solar cell, which seriously hinders the commercial application of perovskite solar cells. At the same time, lead-based perovskites may have the risk of lead leakage, especially in the application of wearable flexible perovskite solar cells. There are safety hazards. The problem of insufficient mechanical stability of the perovskite layer, such as repeated bending or stretching in the outside world, may form macroscopic film cracks or microscopic lattice distortions, which will lead to reduced device performance, which limits its application in flexible devices.

[0003] In view of the above situation, there are studies on adding internal encapsulation additives to the interface between perovskite cells or within the layers to solve the stability problem of the battery. For example, Mina et al. used atomic layer deposition to deposit an aluminum oxide / silicon oxide barrier layer at the interface between the hole transport layer and the electrode. The device maintained 90% of its initial performance after 1000 hours at room temperature and 60% RH. Chen et al. dissolved phospholipid molecules in an isopropanol solution and spin-coated them on the perovskite interface to form a polymer encapsulation layer, which can improve the mechanical stability of the device. After 10,000 bends, it can still maintain 80% of the initial performance, and can inhibit about 90% of lead leakage. Gao et al. synthesized a hydroxyl-containing Spiro-OMeTAD analogue, introduced it into the perovskite / hole transport layer interface, and used it to react with isocyanate to form a polymer encapsulation layer. At room temperature and 60% RH, it can maintain 80% of the initial performance after 3000 hours. Wang et al. directly dissolved polyvinyl pyrrolidone / polyvinyl alcohol blend in perovskite precursor solution as the inner encapsulation layer of perovskite layer, and the device maintained more than 80% of the initial performance after 720 hours at room temperature and 70% RH. Based on this, the present invention provides an internal encapsulation method of perovskite solar cells based on in-situ polymerization, which introduces acrylate and thermal initiator into the perovskite layer, forms an internal in-situ encapsulation in the perovskite film, improves the humidity stability and mechanical stability of perovskite solar cells, and inhibits lead leakage. Summary of the invention

[0004] The purpose of the present invention is to provide a method for internal packaging of perovskite solar cells based on in-situ polymerization. By introducing acrylate and thermal initiator into perovskite precursor, polymerization can be quickly completed during the perovskite annealing process. The formed polymer structure can improve the water vapor resistance of the perovskite layer and offset part of the external stress, thereby improving the humidity stability and mechanical stability of the perovskite solar cell. At the same time, it can effectively inhibit the lead leakage of the lead-based perovskite solar cell and improve biosafety.

[0005] To achieve the above object, the present invention provides a method for internal packaging of a perovskite solar cell based on in-situ polymerization, comprising the following steps:

[0006] S1. preparing a charge transport layer 1 on a conductive substrate;

[0007] S2, preparing a perovskite layer on the charge transport layer 1 of S1, introducing a polymer inner encapsulation layer into the perovskite layer, wherein the polymer inner encapsulation layer is formed by polymerization reaction of acrylate and thermal initiator;

[0008] S3, preparing a second charge transport layer on the perovskite layer of S2;

[0009] S4. Prepare a back electrode on the second charge transport layer of S3.

[0010] Preferably, the conductive substrate in S1 includes a substrate and a transparent conductive electrode disposed on the substrate, the substrate is a rigid substrate or a flexible substrate, and the transparent conductive electrode includes one or more of indium tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide.

[0011] Preferably, the rigid substrate is a glass substrate or a quartz substrate; and the flexible substrate is a polyethylene terephthalate substrate, a polyethylene naphthalate substrate or a transparent polyimide substrate.

[0012] Preferably, the charge transport layer 1 in S1 is an electron transport layer 1 or a hole transport layer 1, the components of the electron transport layer 1 include one or more of tin oxide, titanium oxide, and zinc oxide, and the components of the hole transport layer 1 include one or more of nickel oxide, polytriarylamine, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), and self-assembled monolayers.

[0013] Preferably, the perovskite layer in S2 is prepared by a one-step method or a two-step method, and the annealing temperature of the perovskite layer is 100°C-150°C; the components in the perovskite layer are ABX3, A includes one or more of formamidine, methylamine, ethylamine, and cesium ions, B includes one or more of lead, tin, and germanium ions, and X includes one or more of chlorine, bromine, and iodine ions.

[0014] Preferably, the acrylate in S2 includes one of monoacrylate, diacrylate and triacrylate, wherein the diacrylate includes one of diethylene glycol diacrylate, tetraethylene glycol diacrylate and tricyclodecane dimethanol diacrylate.

[0015] Preferably, the thermal initiator in S2 comprises one of a peroxide initiator, a persulfate initiator or an azo initiator.

[0016] Preferably, the peroxide initiator includes one of methyl ethyl ketone peroxide and lauroyl peroxide; the persulfate initiator includes one of potassium persulfate and ammonium persulfate; and the azo initiator includes one of azobisisobutyronitrile and azobisisoheptylonitrile.

[0017] Preferably, the charge transport layer 2 in S3 is a hole transport layer 2 or an electron transport layer 2, the components of the hole transport layer 2 include one or more of polytriarylamine, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, cuprous iodide, cuprous thiocyanate, and carbon nanotubes, and the components of the electron transport layer 2 include one or more of C60 and its derivatives, tin oxide, and BCP.

[0018] Preferably, the back electrode in S4 includes one or more of gold, silver, aluminum, copper, nickel, and indium tin oxide.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention introduces acrylate molecules and a trace amount of thermal initiator into the perovskite precursor solution. During the annealing process, the thermal initiator is cleaved to generate free radicals, which then initiates the rapid in-situ polymerization of the acrylate molecules to form a polymer structure with a certain hydrophobicity. The hydrophobic polymer is distributed on the perovskite grain boundary and grain surface, thereby improving the water vapor resistance of the perovskite layer and thus improving the stability of the perovskite layer.

[0021] (2) The acrylate used in the present invention has a flexible alkyl chain that can offset part of the external stress, thereby improving the mechanical properties of the perovskite layer; at the same time, the carbonyl group of the acrylate can chelate lead ions, which can effectively inhibit the lead leakage of the lead-based perovskite solar cell, and realize the in-situ internal encapsulation of the perovskite solar cell;

[0022] (3) The internal packaging method of the present invention has a simple preparation process, high repeatability and low cost. After optimizing the concentration parameters, the humidity stability of the prepared perovskite solar cell is greatly improved. Under the condition of 75%±5% RH, the perovskite solar cell after internal packaging can maintain more than 90% of the initial efficiency after being placed for more than 500 hours without external packaging.

[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structure of the perovskite solar cell of the present invention and a schematic diagram of the principle of in-situ polymerization of diethylene glycol diacrylate during the annealing process of the perovskite layer;

[0025] Figure 2 The current density-voltage curves of the perovskite solar cells prepared in Example 1 of the present invention and Comparative Example 1;

[0026] Figure 3 The current density-voltage curves of the perovskite solar cells prepared in Example 2 of the present invention and Comparative Example 1;

[0027] Figure 4 The current density-voltage curves of the perovskite solar cells prepared in Example 3 of the present invention and Comparative Example 1;

[0028] Figure 5 Graph showing humidity stability test results of the perovskite solar cells prepared in Example 1 of the present invention and Comparative Example 1;

[0029] Figure 6 The infrared spectra of Example 4, Comparative Example 2 and diethyl acrylate of the present invention are shown;

[0030] Figure 7 The water contact angle test results of the perovskite layer prepared in Example 4 of the present invention and Comparative Example 2 are shown;

[0031] Figure 8 The scanning electron microscope results of the perovskite layer prepared in Example 4 of the present invention and Comparative Example 2 before and after humidity aging;

[0032] Fig. 9 Graph showing the lead leakage test results of the perovskite layers prepared in Example 4 of the present invention and Comparative Example 2;

[0033] Fig.10 This is a diagram showing the bending test results of the perovskite solar cells prepared in Example 5 of the present invention and Comparative Example 3. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0035] Example 1

[0036] like Figure 1 As shown, the present invention provides a method for internal packaging of a perovskite solar cell based on in-situ polymerization, comprising the following steps:

[0037] S1. Preparation of electron transport layer on conductive substrate

[0038] S1.1. Cleaning the conductive substrate

[0039] Clean the ITO (indium tin oxide) glass, respectively, with glass detergent, deionized water, isopropyl alcohol, anhydrous ethanol ultrasonic cleaning for 20 minutes, blow dry with dry nitrogen, and then place it under ozone ultraviolet conditions for 15 minutes to obtain an ITO substrate for use;

[0040] S1.2. Preparation of electron transport layer 1

[0041] A 15% tin oxide hydrocolloid dispersion was mixed with deionized water at a volume ratio of 1:5, and the tin oxide colloid was completely dispersed in the water by low temperature ultrasonic treatment for 30 minutes; the colloid solution was then ultrasonically dispersed and then evenly spin-coated on an ITO substrate at a spin-coating speed of 4000 rpm; after spin-coating, the tin oxide was annealed at 150° C. for 30 minutes to obtain a tin oxide electron transport layer 1, and then the tin oxide was treated under ozone ultraviolet conditions for 15 minutes;

[0042] S2, preparing a perovskite layer on the charge transport layer 1 of S1, introducing a polymer inner encapsulation layer into the perovskite layer, wherein the polymer inner encapsulation layer is formed by polymerization reaction of acrylate and thermal initiator;

[0043] S2.1. Dissolve lead iodide in a solvent to prepare a lead iodide solution with a concentration of 1.3 mol / L. The solvent is a mixed solvent of dimethylformamide and dimethyl sulfoxide in a volume ratio of 9:1. Stir overnight at room temperature and set aside.

[0044] The lead iodide solution is evenly coated on the tin oxide electron transport layer 1, and the coating is performed at a speed of 1500 rpm for 30 seconds, followed by annealing at 70° C. for 1 minute to obtain a lead iodide film;

[0045] S2.2, dissolving iodoformamidine in a solvent to prepare an iodoformamidine solution with a concentration of 0.35 mol / L, the solvent being isopropanol, the iodoformamidine solution also being doped with bromomethylamine and chloromethylamine, the content of bromomethylamine and chloromethylamine being 10% of the mass fraction of iodoformamidine; then adding diethylene glycol diacrylate to the iodoformamidine solution at a concentration of 3 mg / mL, and adding azobisisobutyronitrile with a mass of 1% of diethylene glycol diacrylate as a thermal initiator, to obtain an iodoformamidine mixed solution for standby use;

[0046] The substrate coated with the lead iodide film was rotated at a speed of 1500 rpm, and then the iodoformamidine mixed solution was continuously and rapidly added to the rotating lead iodide film. After the spin coating was completed, it was quickly transferred to a relative humidity of 30%-40%, and annealed at 150°C for 15 minutes to form a perovskite layer with a cross-linked inner encapsulation layer.

[0047] S3, preparing a hole transport layer II on the perovskite layer of S2

[0048] A 60 mmol / L 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) solution was prepared, and the solvent was chlorobenzene; wherein 35 μL TBP (4-tert-butylpyridine), 18 μL Li-TFSI (lithium bis(trifluoromethylsulfonyl)imide, 520 mg / mL, solvent was acetonitrile), and 8.5 μL FK209 (tri[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt tris(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide, 370 mg / mL, solvent was acetonitrile) were added to each 1 mL Spiro-OMeTAD solution; the Spiro-OMeTAD solution was evenly coated on the perovskite layer, and spin-coated at a speed of 3000 rpm for 30 seconds to obtain a second hole transport layer.

[0049] S4. Thermally evaporate a gold electrode with a thickness of 120 nm on the second hole transport layer of S3 to form a metal electrode, thereby finally obtaining an internally encapsulated perovskite solar cell.

[0050] Comparative Example 1

[0051] The difference from Example 1 is that in step S2.2, diethylene glycol diacrylate and azobisisobutyronitrile are not added to the iodoformamidine solution, and the other components are the same as those in Example 1.

[0052] Photoelectric performance test:

[0053] Under the condition of AM1.5, the photoelectric performance of perovskite solar cells was tested; Figure 2 As shown, the photoelectric performance parameters of the perovskite solar cell obtained in Example 1 are: open circuit voltage 1.14V, short circuit current density 23.87mA / cm 2 , the filling factor is 78.94%, and the photoelectric conversion efficiency is 21.50%; the photoelectric performance parameters of the perovskite solar cell obtained in comparative example 1 are: open circuit voltage 1.13V, short circuit current density 22.34mA / cm 2 , the filling factor is 78.00%, and the photoelectric conversion efficiency is 19.77%; compared with Comparative Example 1, the performance of the perovskite solar cell obtained in Example 1 is greatly improved.

[0054] Humidity stability test

[0055] The perovskite solar cell was placed at room temperature (25°C) and a relative humidity of 75% ± 5%, and was transferred to a nitrogen glove box for testing at regular intervals; Figure 5 As shown, after 530 hours, the average efficiency of the perovskite solar cell obtained in Example 1 can still be maintained at 90% of the initial efficiency, while after 530 hours, the average efficiency of Comparative Example 1 is reduced to less than 20% of the initial efficiency, which proves that the internal encapsulation of diethylene glycol diacrylate in the present invention improves the humidity stability of the perovskite solar cell.

[0056] Example 2

[0057] Taking Example 1 as a benchmark, the difference from Example 1 is that the concentration of diethylene glycol diacrylate in step S2.2 is 1 mg / mL, and the rest is the same as Example 1.

[0058] Photoelectric performance test:

[0059] Under the condition of AM1.5, the photoelectric performance of perovskite solar cells was tested; Figure 3 As shown, the photoelectric performance parameters of the perovskite solar cell obtained in Example 2 are: open circuit voltage 1.14V, short circuit current density 22.97mA / cm 2 , the filling factor is 78.55% and the photoelectric conversion efficiency is 20.64%.

[0060] Example 3

[0061] Taking Example 1 as a benchmark, the difference from Example 1 is that the concentration of diethylene glycol diacrylate in step S2.2 is 5 mg / mL, and the rest is the same as Example 1.

[0062] Photoelectric performance test:

[0063] Under the condition of AM1.5, the photoelectric performance of perovskite solar cells was tested; Figure 4 As shown, the photoelectric performance parameters of the perovskite solar cell obtained in Example 3 are: open circuit voltage 1.12V, short circuit current density 23.85mA / cm 2 , the filling factor is 76.15% and the photoelectric conversion efficiency is 20.38%.

[0064] Example 4

[0065] S1. Clean the glass substrate by ultrasonic cleaning with glass detergent, deionized water, isopropanol, and anhydrous ethanol for 20 minutes each, blow dry with dry nitrogen, and then place it under ozone ultraviolet conditions for 15 minutes to obtain a clean glass substrate for use;

[0066] S2, preparing a perovskite layer on the glass substrate of S1, introducing a polymer inner encapsulation layer into the perovskite layer, wherein the polymer inner encapsulation layer is formed by polymerization reaction of acrylate and thermal initiator;

[0067] S2.1 Dissolve lead iodide in a solvent to prepare a lead iodide solution with a concentration of 1.3 mol / L. The solvent is a mixed solvent of dimethylformamide and dimethyl sulfoxide in a volume ratio of 9:1. Stir overnight at room temperature and set aside.

[0068] The lead iodide solution is evenly coated on the tin oxide electron transport layer, and the coating is performed at a speed of 1500 rpm for 30 seconds, followed by annealing at 70° C. for 1 minute to obtain a lead iodide film;

[0069] S2.2 Dissolve iodoformamidine in a solvent to prepare an iodoformamidine solution with a concentration of 0.35 mol / L, wherein the solvent is isopropanol, and the iodoformamidine solution is also doped with bromomethylamine and chloromethylamine, and the content of bromomethylamine and chloromethylamine is 10% of the mass fraction of iodoformamidine; then add diethylene glycol diacrylate in an amount of 3 mg / mL to the iodoformamidine solution, and add azobisisobutyronitrile with a mass of 1% of diethylene glycol diacrylate as a thermal initiator to obtain an iodoformamidine mixed solution for standby use;

[0070] The substrate coated with the lead iodide film was rotated at a speed of 1500 rpm, and then the iodoformamidine mixed solution was continuously and rapidly added to the rotating lead iodide film. After the spin coating was completed, it was quickly transferred to a relative humidity of 30%-40%, and annealed at 150°C for 15 minutes to form a perovskite layer cross-linked with an inner encapsulation layer.

[0071] Comparative Example 2

[0072] The difference from Example 4 is that in step S2.2, diethylene glycol diacrylate and azobisisobutyronitrile are not added to the iodoformamidine solution, and the other steps are the same as those in Example 4.

[0073] Fourier transform infrared spectroscopy

[0074] Fourier transform infrared spectroscopy analysis was performed on Example 4, Comparative Example 2 and diethylene glycol diacrylate. Figure 6 As shown, it can be seen that the newly appeared peak in Example 4 proves that diethylene glycol diacrylate is successfully introduced into the perovskite layer. At the same time, the movement of the carbonyl characteristic peak to the low wave number direction proves that it interacts with the lead ions. No obvious characteristic peak of the carbon-carbon double bond is detected in Example 4, which proves that diethylene glycol diacrylate successfully completes the in-situ polymerization reaction in the perovskite layer.

[0075] Contact angle test

[0076] The contact angle test was performed on the perovskite layers prepared in Example 4 and Comparative Example 2. Figure 7 As shown,

[0077] The water contact angle of the perovskite layer prepared in Example 4 is 67.3°, and the water contact angle of the perovskite layer prepared in Comparative Example 2 is 57.4°. Compared with Comparative Example 2, the hydrophobicity of the perovskite layer prepared in Example 4 is significantly improved.

[0078] Humidity aging

[0079] The perovskite layers prepared in Example 4 and Comparative Example 2 were placed at room temperature (25° C.) and a relative humidity of 75%±5% for 120 hours for humidity aging; Figure 8 As shown, Figure 8 The SEM images of the perovskite layer prepared in Example 4 and Comparative Example 2 before and after aging are respectively shown. It can be seen that the morphology of the perovskite layer in Example 4 does not change significantly before and after aging, while the morphology of the perovskite layer in Comparative Example 2 after aging shows relatively obvious degradation and aging, which proves that the internal encapsulation of the diethylene glycol diacrylate of the present invention can enhance the water vapor resistance of the perovskite film.

[0080] Lead leakage test

[0081] The perovskite layers prepared in Example 4 and Comparative Example 2 were immersed in deionized water at pH = 7 for 1-20 min, and the lead ion concentration in the water was measured respectively; Fig. 9 As shown, after the perovskite layer of Example 4 is immersed, the lead ion concentration in the water increases slowly and less, while after the perovskite layer of Comparative Example 2 is immersed, the lead ion concentration in the water increases rapidly and reaches an extreme value. The lead ion concentration of the perovskite layer prepared in Example 4 is greatly reduced relative to that in Comparative Example 2, with a reduction of about 70%, proving that the internal encapsulation of diethylene glycol diacrylate of the present invention has the ability to inhibit lead leakage.

[0082] Example 5

[0083] Taking Example 1 as a reference, the difference from Example 1 is that the substrate in step S1.1 is an ITO / PET flexible substrate, and the rest is the same as Example 1.

[0084] Comparative Example 3

[0085] The difference from Example 5 is that in step S2.2, diethylene glycol diacrylate and azobisisobutyronitrile are not added to the iodoformamidine solution, and the other steps are the same as those in Example 5.

[0086] The perovskite solar cells prepared in Example 5 and Comparative Example 3 were subjected to a bending test.

[0087] The perovskite solar cell was bent with a bending radius of 5 mm, and the photoelectric performance was tested after a certain number of bends; Fig.10As shown, the perovskite solar cell prepared in Example 5 can maintain more than 80% of the initial performance after being bent 10,000 times, while the performance of the perovskite solar cell prepared in Comparative Example 3 is reduced to less than 20% of the initial value after being bent 10,000 times, proving that the internal encapsulation of the diethylene glycol diacrylate of the present invention improves the mechanical stability of the perovskite solar cell.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for internal packaging of perovskite solar cells based on in-situ polymerization, characterized in that: The following steps are involved: S1. preparing a charge transport layer 1 on a conductive substrate; S2, preparing a perovskite layer on the charge transport layer 1 of S1, introducing a polymer inner encapsulation layer into the perovskite layer, wherein the polymer inner encapsulation layer is formed by polymerization reaction of acrylate and thermal initiator; S3, preparing a second charge transport layer on the perovskite layer of S2; S4. Prepare a back electrode on the second charge transport layer of S3.

2. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 1, characterized in that: The conductive substrate in S1 includes a substrate and a transparent conductive electrode arranged on the substrate, the substrate is a rigid substrate or a flexible substrate, and the transparent conductive electrode includes one or more of indium tin oxide, fluorine-doped tin oxide, and aluminum-doped zinc oxide.

3. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 2, characterized in that: The rigid substrate is a glass substrate or a quartz substrate; the flexible substrate is a polyethylene terephthalate substrate, a polyethylene naphthalate substrate or a transparent polyimide substrate.

4. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 1, characterized in that: The charge transport layer 1 in S1 is an electron transport layer 1 or a hole transport layer 1, the components of the electron transport layer 1 include one or more of tin oxide, titanium oxide, and zinc oxide, and the components of the hole transport layer 1 include one or more of nickel oxide, polytriarylamine, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), and self-assembled monolayer.

5. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 1, characterized in that: The perovskite layer in S2 is prepared by a one-step method or a two-step method, and the annealing temperature of the perovskite layer is 100°C-150°C; the components in the perovskite layer are ABX3, A includes one or more of formamidine, methylamine, ethylamine, and cesium ions, B includes one or more of lead, tin, and germanium ions, and X includes one or more of chlorine, bromine, and iodine ions.

6. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 1, characterized in that: The acrylate in S2 includes one of monoacrylate, diacrylate and triacrylate, wherein the diacrylate includes one of diethylene glycol diacrylate, tetraethylene glycol diacrylate and tricyclodecane dimethanol diacrylate.

7. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 1, characterized in that: The thermal initiator in S2 includes one of a peroxide initiator, a persulfate initiator or an azo initiator.

8. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 7, characterized in that: The peroxide initiator includes one of methyl ethyl ketone peroxide and lauroyl peroxide; the persulfate initiator includes one of potassium persulfate and ammonium persulfate; the azo initiator includes one of azobisisobutyronitrile and azobisisoheptylnitrile.

9. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 1, characterized in that: The charge transport layer 2 in S3 is a hole transport layer 2 or an electron transport layer 2, and the components of the hole transport layer 2 include one or more of polytriarylamine, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, cuprous iodide, cuprous thiocyanate, and carbon nanotubes, and the components of the electron transport layer 2 include one or more of C60 and its derivatives, tin oxide, and BCP.

10. The method for internal packaging of a perovskite solar cell based on in-situ polymerization according to claim 1, characterized in that: The back electrode in S4 includes one or more of gold, silver, aluminum, copper, nickel, and indium tin oxide.

Citation Information

Cited By

  • Perovskite solar cell based on pentafluorophenol acrylate modification and preparation method thereof

    CN119855364A